The effect of serum pretreatment regimens for the detection of HLA class I antibodies in platelet‐refractory patients. Issue 3 (17th January 2020) - Tumer, Gizem; Gniadek, Thomas; Baye, Jennifer; Pena, Ryan; Warner, Paul; Fung, Mark; Beaudin, Lynette; Dunckley, Heather; Gandhi, Manish; Gathof, Birgit; Hsu, Susan; Klohe, Ellen; et al.
Abstract : BACKGROUND: Single antigen bead (SAB) assays are used to identify human leukocyte antigen (HLA) antibodies in patients with platelet refractoriness due to HLA Class I alloimmunization. Some laboratories use serum pretreatment regimens to eliminate interference from immunoglobulin M antibodies and complement. These modifications may contribute to interlaboratory variability, which is a recognized problem with the SAB assay. STUDY DESIGN AND METHODS: Five patientsʼ sera were overnight shipped to 12 laboratories in the United States and internationally. Recipients used their labʼs SAB procedure to identify HLA Class I antibodies. The resultant mean fluorescence intensity (MFI) data were compared by instrumentation, bead lot, and pretreatment regimens. Laboratory‐specific cutoffs for positive antibodies were applied to the results. RESULTS: Interlaboratory variability for MFI values appears to be associated with different pretreatment regimens. The coefficient of variation (CV) of MFI from samples pretreated with ethylenediaminetetraacetic acid, dithiothreitol, or heat inactivation (EDHI) were similar, ranging from 14% to 56% (mean, 22%). For samples with no pretreatment, the CVs were significantly higher than EDHI‐treated samples, ranging from 25% to 74% (mean, 39%; 95% confidence interval, 12.10‐21.90; p < 0.0001). An intralaboratory comparison of pretreatment regimens confirmed these findings. Some positive antibody specificities present in EDHI‐treated samples were negative in corresponding samples with no pretreatment when laboratory‐specific cutoffs for positive antibodies were applied. CONCLUSION: Our results show that greater interlaboratory precision can be achieved when samples are pretreated with EDHI as opposed to no pretreatment, likely because these pretreatments eliminate interference from inhibitors. Inhibitors may mask antibodies, leading to missed (or uncalled) specificities when no pretreatment is used.